<span>(i) -2x+2y+3z=0 </span><span>(ii) -2x-y+z=-3 </span>(iii) <span>2x+3y+3z=5 </span><span>_________ Sum up the first and the third equation: </span>(i) -2x+2y+3z=0 (iii) 2x+3y+3z=5 _________ 5y + 6z = 5
Sum up the second and the third equation: (ii) -2x-y+z=-3 (iii) 2x+3y+3z=5 _________ 2y + 4z = 2
(iv) 5y + 6z = 5 (v) 2y + 4z = 2 ________ Divide the fifth equation by 2 (iv) 5y + 6z = 5 (v) y + 2z = 1 ________ Multiple the second equation by -3 and sum the equation (iv) 5y + 6z = 5 (v) -3y - 6z = -3 ________ 2y = 2 y = 2/2 = 1
<span>(i) x-y-z=-8 (ii) -4x+4y+5z=7 (iii) 2x+2z=4 ______ </span>Divide the third equation by 2 and rewrite z in the term of x: (iii) x+z=2 z = 2 - x ______ Substitute z from the third equation and express y in the term of x: <span>x-y-(2-x)=-8 x - y - 2 + x = 8 2x - y = 10 y = 2x - 10 ______ Substitute z from the third equation and y from the first equation into the second equation: </span><span>-4x + 4y + 5z = 7 -4x + 4(2x - 10) + 5(2 - x) = 7 -4x + 8x - 40 + 10 - 5x = 7 -x -30 = 7 -x = 30 + 7 x = -37 y = 2x - 10 = 2*(-37) - 10 = -74 - 10 = -84 z = 2 - x = 2 - 37 = -35</span>
the ratio of ten more than three times a number to the square of the same number is equal to ... Write an expression for the number of circles in the Nth figure.